GAMBARAN PERAN KELUARGA DALAM KEBUTUHAN ACTIVITY DAILY LIVING PASIEN STROKE DI WILAYAH KERJA PUSKESMAS RAWASARI KOTA JAMBI - Cika Purnama Fitri; Kamariyah; Suryadi Imran (Jurnal Multidisipliner Kapalamada, 2026)
Stroke is a life-threatening condition that can affect the body and reduce the patient's ability to perform daily activities. The phenomenon that occurs in stroke patients in the Rawasari Community Health Center, Jambi City, shows that patients experience limitations in meeting their needs, so they need family assistance in the care process. The family has an important role as the primary caregiver at home in helping to meet patient needs, support the rehabilitation process, and improve the quality of life of stroke patients. This study aims to describe the role of families in supporting stroke patients with activities of daily living at the Rawasari Community Health Center, Jambi City. A descriptive quantitative research design was used. This study was conducted to provide insight into the role of family members in supporting stroke survivors with daily activities in the Rawasari Community Health Center service environment, Jambi City. A descriptive quantitative research design was used. This study was conducted to provide insight into the role of family members in supporting stroke survivors that measured the role of families in supporting stroke patients with activities of daily living based on the Katz D Index scale, which measures the level of moderate dependency. The results of the study showed that the majority of respondents 67 years old, totaling 7 people (20.0%), and male respondents were the largest group with 18 people (51.4%). The findings regarding family involvement in Activity Daily Living care for stroke patients showed that most families had a good level of role, with 30 respondents (85.7%), followed by a sufficient category with 5 respondents (14.3%), and no families were categorized as having a poor role. Family involvement is crucial in helping stroke patients perform activities of daily living. Adequate family support can help patients carry out daily activities, encourage the recovery process, and improve patient independence.